Identification and estimation of thresholds in the fixed effects ordered logit model - Gregori Baetschmann (University of Zurich, Department of Economics, 2011)
The paper proposes a new estimator for the fixed effects ordered logit model. In contrast to existing methods, the new procedure allows estimating the thresholds. The empirical relevance and simplicity of implementation is illustrated in an application to the effect of unemployment on life satisfaction.
Keywords: C23; C25; J28; J64; 330; ordered response; panel data; correlated heterogeneity; incidental parameters; Logit-Modell; Panel; Theorie